Application of Round Robin Brainstorming Type Cooperative Learning Model to Improve Learning Outcomes of Grade 3 Students of Tunas Daud Christian Elementary School - Usniati, Usniati; astuti, Intan Dwi H; Yanuartri, Dian (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This classroom action research was motivated by the low grades and activeness of students in class during thematic learning, especially in learning mathematics. At the pre-cycle stage it is It should be noted that students have a high yield, which is 59.5 with a 33% satisfaction rate. Therefore, this research was conducted using the Round Robin Brainstorming cooperative learning model in the thematic learning of grade 3 SDK Tunas Daud in the 2022/2023 academic year. Classroom Action Research (PTK) was carried out in two cycles, namely on August 9, 2022 and September 13, 2022. The results of the study showed that in cycle 1 the average score of students' formative test results was 71.8 with a passing percentage of 55%, while in cycle 2. The average score of the students' formative test results is 83.5% with a passing percentage of 80%. Through the APKG 1 and APKG 2 sheets there was also an increase. In cycle 1 the average value of APKG 1 is 4.05 with a percentage of 81% and APKG 2 is 4.27 with a percentage of 85.4%. In cycle 2 the average value of APKG 1 is 4.78 with a percentage of 95.6% and APKG 2 is 4.70 with a percentage of 94%. Thus this shows that the teacher's performance in cycle II has reached the performance indicators set out in the lesson plan. So the cooperative learning model of the Round Robin Brainstorming type succeeded in increasing the learning outcomes of grade 3 students at SDK Tunas Daud